A method for preparing an isothermal methanation catalyst

By combined with water heat treatment and sodium carbonate neutralization, prepare a temperature methane synthetic catalyst with high stability and mechanical strength, solve the problem of poor stability of traditional catalysts, and achieve efficient CO and CO2 conversion.

CN116020470BActive Publication Date: 2025-01-21SINOPEC NANJING RES INST OF CHEM IND CO LTD +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111238254.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-25
Publication Date
2025-01-21
Estimated Expiration
2041-10-25

AI Technical Summary

Technical Problem

Under the conditions of isothermal fixed bed reactors, the traditional methane synthesis catalyst has poor stability, poor mechanical strength, and easy carbon formation, making it difficult to ensure the activity and stability of long-term use.

Method used

Using a combination of hydrothermal treatment process and sodium carbonate neutralization process, Al synergizes with metals such as Mg, La, Zn, Zr, Ce, Mn, etc. to prepare a carrier, and the active component Ni is highly dispersed on the carrier to form a carrier with a good specific surface area and pore size of the catalyst.

Benefits of technology

The stability and mechanical strength of the catalyst are improved, the specific surface area and pore size change before and after use are small, there is no carbon deposition, and the CO and CO2 conversion rate reaches more than 99.0%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 821174DEST_PATH_IMAGE004
    Figure 821174DEST_PATH_IMAGE004
  • Figure 904034DEST_PATH_IMAGE002
    Figure 904034DEST_PATH_IMAGE002
Patent Text Reader

Abstract

The present invention belongs to the field of catalytic technology, and relates to an isothermal methanation catalyst and a preparation method thereof. A hydrothermal treatment process is combined with a sodium carbonate neutralization process, and the prepared carrier has good specific surface area and pore size, and heat and mass transfer performance through the synergistic effect of Al and multi-metal components such as Mg, La, Zn, Zr, Ce, and Mn. Nitric acid is used to modulate the nickel nitrate solution impregnation process, and the active component Ni is highly dispersed on the carrier. The prepared catalyst has good activity and stability, which solves the problems of poor heat and mass transfer performance, poor stability, poor mechanical strength, and easy carbon deposition of traditional methane synthesis catalysts under the conditions of an isothermal fixed bed reactor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysis, and in particular relates to a method for preparing an isothermal methanation catalyst. Background Art

[0002] Due to the scarcity of natural gas resources in my country, the technology of using coke oven gas to produce natural gas is gaining more and more attention. Compared with the process routes of producing methanol and synthetic ammonia from coke oven gas, the production of natural gas from coke oven gas has the advantages of low investment and good economic benefits. Its by-product hydrogen can also be used to produce synthetic ammonia, so the production of natural gas from coke oven gas is the development direction of the comprehensive utilization of coke oven gas.

[0003] Methanation technology is one of the key technologies for producing natural gas from coke oven gas. There are currently two types of methanation reaction processes in industrial production, multi-stage adiabatic and single-stage isothermal. Compared with multi-stage adiabatic methanation technology, single-stage isothermal methanation reaction technology has a shorter process flow, omitting the circulating gas compressor and decarbonization processes, fewer reactors, and less investment. The methanation part can reduce investment by more than 70%. This process has a high tolerance for CO and CO2 in the raw gas and strong adaptability, and can supplement carbon to increase CH4 production.

[0004] Chinese patent CN105195160A describes an isothermal methanation catalyst and its preparation method. The patent uses a composite oxide formed by magnesium, aluminum and silicon as a shaped catalyst carrier and nickel as an active component. -1 , it shows good low-temperature activity in an isothermal fixed bed with a pressure of 2.0Mpa, a temperature of 400℃, and an inlet gas of CO: 3.63%, CO2: 1.3%. However, the patent adopts an extrusion molding method to obtain the carrier. Although the carrier has a good surface area and abundant pores, the strength of the extruded catalyst is low, and the activity and stability of the catalyst are difficult to guarantee for long-term use, and the stability of the catalyst is not mentioned in the patent.

[0005] At present, isothermal methanation has attracted more and more attention from domestic and foreign research institutes due to its short process flow and low energy consumption. Developing a stable and efficient methanation catalyst as one of the key technologies of isothermal methanation is an important issue that researchers need to solve. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing an isothermal methane synthesis catalyst, which solves the problems of poor stability, poor mechanical strength, easy carbonization, etc. of traditional methane synthesis catalysts under the conditions of an isothermal fixed bed reactor.

[0007] The main features of the present invention are:

[0008] (1) By combining the hydrothermal treatment process with the sodium carbonate neutralization process, Al and metals such as Mg, La, Zn, Zr, Ce, and Mn work synergistically to prepare a carrier with good specific surface area and pore size, and excellent heat and mass transfer performance;

[0009] (2) The active component Ni is highly dispersed on the carrier, and the catalyst has good stability. The specific surface area and pore size of the catalyst change little before and after use, and there is no carbon deposit;

[0010] (3) Under the condition of isothermal non-circulating reaction process, when the coke oven gas composition is CO 6~10%, CO2 2~5%, C2H61~4%, H2 55~60%, the balance is N2, and the space velocity is 5000~10000h -1 Under the conditions of pressure 1.5~3.0MPa and temperature 250~400℃, the conversion rates of CO and CO2 reached more than 99.0% respectively.

[0011] The present invention provides a method for preparing an isothermal methanation catalyst, characterized in that the catalyst is obtained by the following steps:

[0012] Preparation of the carrier: Pseudo-boehmite and metal X nitrate are dissolved in deionized water under stirring at room temperature to 60°C, and then added into a polytetrafluoroethylene-lined autoclave after being stirred evenly, and γ-Al2O3 is added, and the pH value of the solution is adjusted to 5.5 to 6.5 by adding 0.02 to 0.1 mol / L nitric acid, and hydrothermal treatment is performed after increasing the temperature and pressure; the solution after the hydrothermal treatment is neutralized with a sodium carbonate solution, and the pH value of the end point is controlled to be 8.5; the neutralized material is dried, pressed into tablets, and calcined at 500 to 800°C for 4 to 5 hours to obtain the carrier.

[0013] Preparation of active components: Dissolve Ni(NO3)2•6H2O in water, add 0.02~0.1mol / L nitric acid to a pH value of 5.5~6.5 to obtain an impregnation solution rich in active components.

[0014] Preparation of catalyst: Control the temperature at 60~90℃, immerse an equal volume of the carrier in the impregnation solution for 1.0~3.0h; take out the impregnated catalyst precursor, dry and calcine to obtain the finished catalyst.

[0015] In the above steps, the metal X nitrate is one or more of magnesium nitrate, lanthanum nitrate, zinc nitrate, zirconium nitrate, cerium nitrate and manganese nitrate.

[0016] The molar ratio of Al:X in the above steps is 1:0.1-0.5.

[0017] The mass ratio of γ-Al2O3 to pseudo-boehmite added in the above steps is 0.1~0.5:1.

[0018] The pH value of the hydrothermal treatment solution in the above steps is 5.5-6.5.

[0019] In the above steps, the hydrothermal treatment temperature is 150-200°C and the pressure is 1.0-2.0MPa.

[0020] The hydrothermal treatment time in the above steps is 1 to 3 hours.

[0021] In the above steps, the concentration of the sodium carbonate solution is 0.5-1.2 mol / L.

[0022] In the above steps, the calcination temperature of the carrier is 450-550°C, and the calcination time is 4-5 hours.

[0023] The specific gravity of the impregnation solution rich in active ingredients in the above steps is 1.40-1.50.

[0024] In the above steps, the calcination temperature of the catalyst precursor is 300-450° C., and the calcination time is 2-3 hours.

[0025] In the above steps, the loading amount of the active component Ni is 10-15% of the catalyst weight.

[0026] A typical laboratory preparation process of the present invention is as follows:

[0027] (1) dissolving 100 g of pseudo-boehmite and 5 to 65 g of metal X nitrate in deionized water at room temperature to 60° C. under stirring, and stirring evenly; (2) adding the solution in step (1) into an autoclave lined with polytetrafluoroethylene, adding 10 to 50 g of γ-Al2O3, adjusting the pH value of the solution to 5.5 to 6.5 by adding 0.02 to 0.1 mol / L nitric acid, and performing a hydrothermal treatment at a temperature of 150 to 200° C. and a pressure of 1.0 to 2.0 MPa for 1 to 3 h after heating and pressure increasing; (3) neutralizing the solution after the hydrothermal treatment in step (2) with a sodium carbonate solution having a concentration of 0.5 to 1.2 mol / L, and controlling the pH value at the end point to be 8.5; (4) drying and tableting the material obtained in step (3), and calcining at 500 to 800° C. for 4 to 5 h to obtain a carrier. (5) Dissolve Ni(NO3)2•6H2O in water, add 0.02~0.1 mol / L nitric acid to a pH value of 5.5~6.5, and obtain an impregnation solution with a specific gravity of 1.40~1.50 and rich in active components; (6) Control the temperature at 60~90℃, and immerse an equal volume of the carrier in the impregnation solution for 1.0~3.0h; take out the impregnated catalyst precursor, dry it, and calcine it at 300~450℃ for 2~3h to obtain the finished catalyst.

[0028] The isothermal bed methane synthesis catalyst prepared by the present invention has a simple preparation method, is conducive to industrial production, and has good activity and stability. DETAILED DESCRIPTION

[0029] The method of the present invention is described in detail below through examples, but the examples are only used to illustrate the invention and do not constitute a limitation on the scope of the present invention.

[0030] Example 1

[0031] (1) Dissolve 100 g of pseudo-boehmite, 10 g of magnesium nitrate, 5 g of lanthanum nitrate and 5 g of zinc nitrate in deionized water at 60° C. and stir evenly; (2) Add the solution in step (1) to an autoclave lined with polytetrafluoroethylene, add 25 g of γ-Al2O3, adjust the pH value of the solution to 6.5 by adding 0.05 mol / L nitric acid, increase the temperature and pressure, and perform hydrothermal treatment at 180° C. and 1.5 MPa for 2 h; (3) Neutralize the solution after the hydrothermal treatment in step (2) with a sodium carbonate solution having a concentration of 1.0 mol / L, and control the pH value at the end point to be 8.5; (4) Dry and tablet the material obtained in step (3), and calcine at 550° C. for 5 h to obtain a carrier. (5) Dissolve Ni(NO3)2•6H2O in water, add 0.05 mol / L nitric acid to a pH value of 6.0, and obtain an impregnation solution rich in active components with a specific gravity of 1.45; (6) Control the temperature at 80°C and immerse an equal volume of the carrier in the impregnation solution for 2.0 h; take out the impregnated catalyst precursor, dry it, and calcine it at 450°C for 2 h to obtain the finished catalyst Y-1.

[0032] Example 2

[0033] (1) Dissolve 100 g of pseudo-boehmite, 15 g of magnesium nitrate, 5 g of lanthanum nitrate and 5 g of cerium nitrate in deionized water at 50° C. and stir evenly; (2) Add the solution in step (1) to an autoclave lined with polytetrafluoroethylene, add 30 g of γ-Al2O3, adjust the pH value of the solution to 6.0 by adding 0.06 ol / L nitric acid, increase the temperature and pressure, and perform hydrothermal treatment at 200° C. and 2.0 MPa for 1.5 h; (3) Neutralize the solution after hydrothermal treatment in step (2) with a sodium carbonate solution having a concentration of 0.8 mol / L, and control the pH value at the end point to be 8.5; (4) Dry and tablet the material obtained in step (3), and calcine at 600° C. for 4 h to obtain a carrier. (5) Dissolve Ni(NO3)2•6H2O in water, add 0.06 mol / L nitric acid to a pH value of 6.5, and obtain an impregnation solution with a specific gravity of 1.50 and rich in active components; (6) Control the temperature at 75°C and immerse an equal volume of the carrier in the impregnation solution for 2.5 h; take out the impregnated catalyst precursor, dry it, and calcine it at 420°C for 3 h to obtain the finished catalyst Y-2.

[0034] Example 3

[0035] (1) Dissolve 100 g of pseudo-boehmite, 10 g of zinc nitrate, 5 g of zirconium nitrate and 10 g of manganese nitrate in ionized water at 40° C. and stir evenly; (2) Add the solution in step (1) to an autoclave lined with polytetrafluoroethylene, add 40 g of γ-Al2O3, adjust the pH value of the solution to 6.0 by adding 0.04 mol / L nitric acid, increase the temperature and pressure, and perform hydrothermal treatment at a temperature of 170° C. and a pressure of 1.8 MPa for 2 h; (3) Neutralize the solution after the hydrothermal treatment in step (2) with a sodium carbonate solution having a concentration of 0.9 mol / L, and control the pH value at the end point to be 8.5; (4) Dry and tablet the material obtained in step (3), and calcine at 650° C. for 5 h to obtain a carrier. (5) Dissolve Ni(NO3)2•6H2O in water, add 0.04 mol / L nitric acid to a pH value of 6.0, and obtain an impregnation solution rich in active components with a specific gravity of 1.40; (6) Control the temperature at 65°C and immerse an equal volume of the carrier in the impregnation solution for 3.0 h; take out the impregnated catalyst precursor, dry it, and calcine it at 400°C for 3 h to obtain the finished catalyst Y-3.

[0036] Example 4

[0037] (1) Dissolve 100 g of pseudo-boehmite and 10 g of magnesium nitrate, 5 g of zirconium nitrate, cerium nitrate and 8 g of manganese nitrate in ionized water at 30° C. and stir evenly; (2) Add the solution in step (1) to an autoclave lined with polytetrafluoroethylene, add 50 g of γ-Al2O3, adjust the pH value of the solution to 5.5 by adding 0.1 mol / L nitric acid, increase the temperature and pressure, and perform hydrothermal treatment at a temperature of 150° C. and a pressure of 2.0 MPa for 3 h; (3) Neutralize the solution after the hydrothermal treatment in step (2) with a sodium carbonate solution having a concentration of 1.2 mol / L, and control the pH value at the end point to be 8.5; (4) Dry and tablet the material obtained in step (3), and calcine at 650° C. for 4 h to obtain a carrier. (5) Dissolve Ni(NO3)2•6H2O in water, add 0.1 mol / L nitric acid to a pH value of 5.5, and obtain an impregnation solution with a specific gravity of 1.40 and rich in active components; (6) Control the temperature at 60°C and immerse an equal volume of the carrier in the impregnation solution for 3.0 h; take out the impregnated catalyst precursor, dry it, and calcine it at 350°C for 3 h to obtain the finished catalyst Y-4.

[0038] Example 5

[0039] (1) Dissolve 100 g of pseudo-boehmite, 5 g of magnesium nitrate, 10 g of cerium nitrate and 10 g of manganese nitrate in ionized water at 40° C. and stir evenly; (2) Add the solution in step (1) to an autoclave lined with polytetrafluoroethylene, add 20 g of γ-Al2O3, adjust the pH value of the solution to 6.2 by adding 0.08 mol / L nitric acid, increase the temperature and pressure, and perform hydrothermal treatment at 200° C. and 1.0 MPa for 1 h; (3) Neutralize the solution after the hydrothermal treatment in step (2) with a sodium carbonate solution having a concentration of 0.85 mol / L, and control the pH value at the end point to be 8.5; (4) Dry and press the material obtained in step (3) into tablets, and calcine at 580° C. for 5 h to obtain a carrier. (5) Dissolve Ni(NO3)2•6H2O in water, add 0.02 mol / L nitric acid to a pH value of 6.5, and obtain an impregnation solution rich in active components with a specific gravity of 0-1.50; (6) Control the temperature at 70°C and immerse an equal volume of the carrier in the impregnation solution for 2.0 h; take out the impregnated catalyst precursor, dry it, and calcine it at 450°C for 2 h to obtain the finished catalyst Y-5.

[0040] Example 6

[0041] (1) Dissolve 100 g of pseudo-boehmite and 25 g of magnesium nitrate in ionized water at room temperature and under stirring, and stir evenly; (2) Add the solution in step (1) into a polytetrafluoroethylene-lined autoclave, add 50 g of γ-Al2O3, adjust the pH value of the solution to 5.5 by adding 0.02 mol / L nitric acid, increase the temperature and pressure, and perform hydrothermal treatment at a temperature of 150° C. and a pressure of 2.0 MPa for 3 h; (3) Neutralize the solution after the hydrothermal treatment in step (2) with a sodium carbonate solution having a concentration of 0.5 mol / L, and control the pH value of the end point to be 8.5; (4) Dry and tablet the material obtained in step (3), and calcine at 600° C. for 5 h to obtain a carrier. (5) Dissolve Ni(NO3)2•6H2O in water, add 0.02 mol / L nitric acid to a pH value of 5.5, and obtain an impregnation solution with a specific gravity of 1.40 and rich in active components; (6) Control the temperature at 70°C and immerse an equal volume of the carrier in the impregnation solution for 3.0 h; take out the impregnated catalyst precursor, dry it, and calcine it at 450°C for 2 h to obtain the finished catalyst Y-6.

[0042] Example 7

[0043] (1) Dissolve 100 g of pseudo-boehmite, 5 g of lanthanum nitrate and 10 g of zinc nitrate in ionized water at 45° C. and stir evenly; (2) Add the solution in step (1) to an autoclave lined with polytetrafluoroethylene, add 40 g of γ-Al2O3, adjust the pH value of the solution to 5.8 by adding 0.03 mol / L nitric acid, increase the temperature and pressure, and perform hydrothermal treatment at a temperature of 160° C. and a pressure of 1.4 MPa for 2.0 h; (3) Neutralize the solution after the hydrothermal treatment in step (2) with a sodium carbonate solution having a concentration of 0.75 mol / L, and control the pH value of the end point to be 8.5; (4) Dry and press the material obtained in step (3) to obtain a carrier. (5) Dissolve Ni(NO3)2•6H2O in water, add 0.03 mol / L nitric acid to a pH value of 5.8, and obtain an impregnation solution with a specific gravity of 1.48 and rich in active components; (6) Control the temperature at 85°C and immerse an equal volume of the carrier in the impregnation solution for 2.0 h; take out the impregnated catalyst precursor, dry it, and calcine it at 400°C for 2.5 h to obtain the finished catalyst Y-7.

[0044] Example 8

[0045] (1) Dissolve 100 g of pseudo-boehmite, 15 g of magnesium nitrate and 10 g of cerium nitrate in ionized water at a temperature of 50° C. and stir evenly; (2) Add the solution in step (1) to an autoclave lined with polytetrafluoroethylene, add 45 g of γ-Al2O3, adjust the pH value of the solution to 6.0 by adding 0.07 mol / L nitric acid, increase the temperature and pressure, and perform hydrothermal treatment at a temperature of 180° C. and a pressure of 1.5 MPa for 2.0 h; (3) Neutralize the solution after the hydrothermal treatment in step (2) with a sodium carbonate solution having a concentration of 1.0 mol / L, and control the pH value at the end point to be 8.5; (4) Dry and tablet the material obtained in step (3), and calcine at 620° C. for 4 h to obtain a carrier. (5) Dissolve Ni(NO3)2•6H2O in water, add 0.007 mol / L nitric acid to a pH value of 6.0, and obtain an impregnation solution with a specific gravity of 1.50 and rich in active components; (6) Control the temperature at 80°C and immerse an equal volume of the carrier in the impregnation solution for 2.0 h; take out the impregnated catalyst precursor, dry it, and calcine it at 400°C for 2 h to obtain the finished catalyst Y-8.

[0046] Example 9

[0047] (1) Dissolve 100 g of pseudo-boehmite, 15 g of magnesium nitrate and 10 g of manganese nitrate in ionized water at 40° C. and stir evenly; (2) Add the solution in step (1) to a polytetrafluoroethylene-lined autoclave, add 25 g of γ-Al2O3, adjust the pH value of the solution to 6.0 by adding 0.05 mol / L nitric acid, increase the temperature and pressure, and perform hydrothermal treatment at a temperature of 175° C. and a pressure of 1.6 MPa for 2 h; (3) Neutralize the solution after the hydrothermal treatment in step (2) with a sodium carbonate solution having a concentration of 0.6 mol / L, and control the pH value at the end point to be 8.5; (4) Dry and tablet the material obtained in step (3), and calcine at 750° C. for 4 h to obtain a carrier. (5) Dissolve Ni(NO3)2•6H2O in water, add 0.05 mol / L nitric acid to a pH value of 6.0, and obtain an impregnation solution rich in active components with a specific gravity of 1.45; (6) Control the temperature at 85°C and immerse an equal volume of the carrier in the impregnation solution for 1.5 h; take out the impregnated catalyst precursor, dry it, and calcine it at 400°C for 3 h to obtain the finished catalyst Y-9.

[0048] Comparative Example 1

[0049] (1) 100g of kaolin, 200g of alumina and 40g of magnesium oxide were mixed evenly, 3% of carboxymethyl cellulose and 1% of tung oil were added and mixed evenly, the obtained mixture was kneaded for 4h, extruded into strips, dried at 90℃ for 12h, and calcined at 1200℃ for 2h to obtain a shaped carrier. (2) A solution containing 10% magnesium nitrate, 1.5% lanthanum nitrate, 10% calcium nitrate, 3% zirconium nitrate and 14% aluminum nitrate was impregnated on the shaped carrier obtained in the above steps, dried at 90℃ for 12h, and calcined and decomposed at 600℃ for 8h; (3) A nickel nitrate solution with a mass fraction of 45% was impregnated on the carrier obtained in step 2, dried at 110℃ for 6h, and calcined and decomposed at 400℃ for 6h; (4) Step 3 was repeated to obtain an isothermal methanation catalyst product D-1.

[0050] Comparative Example 2

[0051] (1) 120g of kaolin, 180g of alumina and 40g of magnesium oxide were mixed evenly, 1% of carboxymethyl cellulose and 4% of tung oil were added and mixed evenly, the obtained mixture was kneaded for 4h, extruded into strips, dried at 100℃ for 8h and calcined at 1000℃ for 6h to obtain a shaped carrier. (2) A solution containing 12% magnesium nitrate, 1% cerium nitrate, 3% zirconium nitrate and 16% aluminum nitrate was impregnated on the shaped carrier obtained in the above steps, dried at 100℃ for 10h, calcined and decomposed at 400℃ for 12h; (3) A nickel nitrate solution with a mass fraction of 45% was impregnated on the carrier obtained in step 2, dried at 120℃ for 4h, calcined and decomposed at 600℃ for 6h; (4) Step 3 was repeated to obtain an isothermal methanation catalyst product D-2.

[0052] Comparative Example 3

[0053] (1) 100 g of pseudo-boehmite was heat treated at 500 °C and then pressed into tablets to obtain an alumina carrier; (2) The carrier was immersed in a Ni(NO3)2 solution at 75 °C for 2 h; (3) The impregnated catalyst precursor was taken out, dried, and calcined at 450 °C for 2 h to obtain the finished catalyst products D-3 with Ni content of 8% and 2%.

[0054] Catalyst performance evaluation

[0055] Examples Y-1 to Y-9 and comparative examples D-1 to D-3 were loaded into an isothermal bed reactor at a temperature of 300°C, a pressure of 3.0 MPa, and a space velocity of 10000 h -1 , samples were taken and analyzed at 72h and 300h under the condition of H2 / CO=3.

[0056] Specific data are shown in Tables 1 and 2 below.

[0057] Table 1 Comparison of catalyst performance between examples and comparative examples

[0058]

[0059] It can be seen from the reaction data in Table 1 that catalysts Y-1~Y-9 prepared by this method showed good CO conversion and CO2 conversion performance after 72h and 300h, and the stability was guaranteed; while comparative examples D-1, D-2, and D-3 showed good conversion performance at 72h, but their conversion and selectivity were greatly reduced after 300h of reaction, proving that the catalyst has poor stability under isothermal bed conditions for long-term operation.

[0060] Table 2 Characterization and analysis of catalysts in Examples and Comparative Examples before and after use

[0061]

[0062] It can be seen from the data in Table 2 that: the analysis of the specific surface area, pore volume and carbon mass fraction of the catalyst before and after 300 hours of use shows that the catalyst prepared by this method changes little after use, and the catalyst has good stability. No blockage or carbon deposition was found on the surface and inside by SEM scanning electron microscopy. However, comparative examples D-1, D-2 and D-3 all showed varying degrees of carbon deposition, which may be the reason why the activity and selectivity of the comparative examples decreased to varying degrees in the later period. In addition, the comparative example showed powdering after 300 hours of operation, and the mechanical strength was significantly reduced.

Claims

1. A method for preparing an isothermal methanation catalyst, characterized in that The steps for preparing the catalyst are as follows: (1) Preparation of carrier: a. Dissolve pseudo-boehmite and metal X nitrate in deionized water at room temperature ~ 60°C and stir evenly; b. The solution in step a is added to a polytetrafluoroethylene-lined autoclave, γ-Al2O3 is added, the pH value of the solution is adjusted by adding 0.02 to 0.1 mol / L nitric acid, and the temperature and pressure are increased before hydrothermal treatment; c. The solution after the hydrothermal treatment in step b was neutralized with a sodium carbonate solution to control the end point pH value to be 8.5; d. The material obtained in step c is dried, tableted, and calcined to obtain a carrier; (2) Preparation of active components: Dissolve Ni(NO3)2•6H2O in water, add 0.02~0.1 mol / L nitric acid to a pH value of 5.5~6.5 to obtain an impregnation solution rich in active components; (3) Preparation of catalyst: Control the temperature at 60-90°C, immerse an equal volume of the carrier in the impregnation solution for 1.0-3.0 hours; take out the impregnated catalyst precursor, dry and calcine it to obtain the finished catalyst; In the carrier preparation step a, the metal X nitrate is one or more of lanthanum nitrate, zinc nitrate, zirconium nitrate, cerium nitrate, and manganese nitrate; In step b of preparing the carrier, the pH value of the solution is 5.5-6.5; the temperature is 150-200° C., the pressure is 1.0-2.0 MPa; and the hydrothermal treatment time is 1-3 h.

2. The preparation method according to claim 1, characterized in that In step a of preparing the carrier, the molar ratio of Al:X in the pseudo-boehmite is 1:(0.1~0.5).

3. The preparation method according to claim 1, characterized in that The mass ratio of γ-Al2O3 to pseudo-boehmite added in step b of the carrier preparation is 0.1~0.5:

1.

4. The preparation method according to claim 1, characterized in that The concentration of the sodium carbonate solution in the carrier preparation step c is 0.5~1.2 mol / L.

5. The preparation method according to claim 1, characterized in that In step d, the calcination temperature of the carrier is 500-800° C., and the calcination time is 4-5 hours.

6. The preparation method according to claim 1, characterized in that The specific gravity of the impregnation solution rich in active ingredients is 1.40~1.

50.

7. The preparation method according to claim 1, characterized in that The calcination temperature of the catalyst precursor is 300~450℃, and the calcination time is 2~3h.

8. The preparation method according to claim 1, characterized in that The loading amount of the active component Ni is 10~15% of the catalyst weight.

Citation Information

Patent Citations

  • Isothermal methanation catalyst and preparation method thereof

    CN105195160A

  • Method for preparing high-stability methanation catalyst carrier

    CN105727920A

  • Preparation method of catalyst for slurry reactor low-temperature methane synthesis reaction

    CN112547067A

  • Coke-oven gas isothermal methanation catalyst and preparation method thereof

    CN113499763A